2021
DOI: 10.1159/000519540
|View full text |Cite
|
Sign up to set email alerts
|

Women and Stroke: Different, yet Similar

Abstract: <b><i>Background:</i></b> The impact of gender on acute ischemic stroke, in terms of presentation, severity, etiology, and outcome, is increasingly getting recognized. Here, we analyzed the gender-related differences in etiology and outcome of ischemic stroke in South India. <b><i>Methods:</i></b> Patients with first ever ischemic stroke within 1 week of onset presenting to the Comprehensive Stroke Care Centre, Sree Chitra Tirunal Institute for Medical Sciences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…13 Then, according to the NIHSS, this study shows that moderate and severe strokes are more common in women, and mild strokes are more common in men. This study is consistent with the findings in a study conducted by Nandini Mitta et al 14 in India, which showed that the NIHSS scores in women tended to be higher than men with a mean ratio of 9.5 vs. 8.4. These findings can be explained because brain aging in women is more sensitive to ischemic events related to hormonal changes, primarily by decreased of estrogen, which causes changes in lipid profiles, insulin, increased blood pressure, and inflammatory and fibrinolytic markers contributing to the formation of atherosclerotic plaques.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…13 Then, according to the NIHSS, this study shows that moderate and severe strokes are more common in women, and mild strokes are more common in men. This study is consistent with the findings in a study conducted by Nandini Mitta et al 14 in India, which showed that the NIHSS scores in women tended to be higher than men with a mean ratio of 9.5 vs. 8.4. These findings can be explained because brain aging in women is more sensitive to ischemic events related to hormonal changes, primarily by decreased of estrogen, which causes changes in lipid profiles, insulin, increased blood pressure, and inflammatory and fibrinolytic markers contributing to the formation of atherosclerotic plaques.…”
Section: Discussionsupporting
confidence: 93%
“…The neurological deficit as a clinical outcome was assessed using the NIHSS during admission and discharge from the hospital with the following classifications: mild (≤6), moderate (7)(8)(9)(10)(11)(12)(13)(14)(15), and severe (≥16). 6,8 The data that has been collected is processed and analyzed using descriptive statistics.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of gender on acute ischemic stroke, in terms of presentation, severity, etiology, and outcome, is increasingly getting recognized. 41 Therefore, Results of our research and previous researches indicate that COVID-19 is likely to have different effects on stroke patients of different gender. However, it is difficult to explain the gender difference in the impact of COVID-19 on stroke patients which were found in our study.…”
Section: Discussionmentioning
confidence: 56%
“…Men were more prone to large artery atherosclerosis, whereas women were more likely to develop cardioembolic strokes due to rheumatic heart disease. 6 As per the Hyderabad stroke registry, the pattern of ischemic stroke subtypes in India is similar to registries from West and East Asian countries. The registry indicates a significant occurrence of large artery and small vessel diseases, with intracranial atherosclerosis being the most prevalent.…”
Section: Stroke Epidemiology Global Versus Indianmentioning
confidence: 70%